The temporal dynamics of metacognition: Dissociating task-related activity from later metacognitive processes. (February 2016) - Desender, Kobe; Van Opstal, Filip; Hughes, Gethin; Van den Bussche, Eva
Abstract: In recent years, neuroscience research spent much effort in revealing brain activity related to metacognition. Despite this endeavor, it remains unclear exactly when metacognitive experiences develop during task performance. To investigate this, the current study used EEG to temporally and spatially dissociate task-related activity from metacognitive activity. In a masked priming paradigm, metacognitive experiences of difficulty were induced by manipulating congruency between prime and target. As expected, participants more frequently rated incongruent trials as difficult and congruent trials as easy, while being completely unable to perceive the masked primes. Results showed that both the N2 and the P3 ERP components were modulated by congruency, but that only the P3 modulation interacted with metacognitive experiences. Single-trial analysis additionally showed that the magnitude of the P3 modulation by congruency accurately predicted the metacognitive response. Source localization indicated that the N2 task-related activity originated in the ACC, whereas the P3-interplay between task-related activation and metacognitive experiences originated from the precuneus. We conclude that task-related activity can be dissociated from later metacognitive processing. Highlights: EEG was used to dissociate task-related activity from metacognitive activity. Metacognition was manipulated by varying prime-target congruency. Both the N2 and the P3 ERP component were modulated by congruency. Only the P3 modulation interacted with metacognitive experiences.